PD‐1/B7‐H1 Interaction Contribute to the Spontaneous Acceptance of Mouse Liver Allograft - Miwa Morita; M Fujino; Guo‐Ping Jiang; Y Kitazawa; Lin Xie; Miyuki Azuma; H Yagita; Shizuko Nagao; Atsushi Sugioka; Yoshikazu Kurosawa; S. Takahara; John J. Fung; et al. (2009)
The programmed death-1 (PD-1)/B7-H1 pathway acts as an important negative regulator of immune responses. We herein investigated the role of the PD-1/B7-H1 pathway in establishing an immunological spontaneous tolerance status in mouse liver allografting. B7-H1 is highly expressed on the donor-derived tissue cells and it is also associated with the apoptosis of infiltrating T cells in the allografts. Strikingly, a blockade of the PD-1/B7-H1 pathway via anti-B7-H1mAb or using B7-H1 knockout mice as a donor led to severe cell infiltration as well as hemorrhaging and necrosis, thus resulting in mortality within 12 days. Furthermore, the expression of the FasL, perforin, granzyme B, iNOS and OPN mRNA in the liver allografts increased in the antibody-treated group in comparison to the controls. Taken together, these data revealed that the B7-H1 upregulation on the tissue cells of liver allografts thus plays an important role in the apoptosis of infiltrating cells, which might play a critical role of the induction of the spontaneous tolerance after hepatic transplantation in mice.